Management of Cooperatives Focusing on Asta-Ja and Globalization - Poudel, Durga (Journal of Comparative International Management, 2018)
Nepal has been experiencing increasing food deficits for the past three decades. Inadequate irrigation facilities, labor shortages, conversion of agricultural lands to other land uses, land degradation, poor agricultural marketing, lack of necessary infrastructures, and poor agricultural productivity are commonly cited constraints to increased agricultural outputs. Cooperatives are one of the three pillars for the economic development of Nepal (public, private, and cooperative). Currently, there are a total of 34,512 cooperatives (13,578 savings and credit, 4,371 multipurpose, 10,921 agriculture, 1,658 milk, 1,423 consumer, 193 fruits and vegetables, 108 tea, 155 coffee, 184 Jadibuti, 93 bee keeping, 143 communication, 128 health, 48 sugarcane, 45 Junar, and 999 other), with a total membership number of 6,305,581 in Nepal. Despite these initiatives, Nepal’s agriculture is experiencing a serious downward spiral. Therefore, it is necessary to immediately identify and implement a theoretically grounded agricultural development framework in order to reverse the downward spiral of agriculture, accelerate economic growth, and achieve fast-paced socio-economic transformation. In this regard, I suggest strengthening cooperatives at the grassroots level for agricultural production within the framework of Asta-Ja (referring to eight Nepali “Ja”- Jal, Jamin, Jungle, Jadibuti, Janashakti, Janawar, Jarajuri, and Jalabayu) and integrating them vertically with public and private businesses at the regional and national level. Agricultural programs and policies need to be formulated so that they would focus locally on Asta-Ja resources and globally on international trade and treaties, global demand and supply, global climate change, the emerging concept of the fourth wave of industrialization, and other pertinent issues within the global context.